X‐ray CT reveals 4D root system development and lateral root responses to nitrate in soil - Marcus Griffiths; Nathan Mellor; Craig J. Sturrock; Brian S. Atkinson; James Johnson; Stefan Mairhofer; Larry M. York; Jonathan A. Atkinson; Mohammadreza Soltaninejad; John F. Foulkes; Michael P. Pound; Sacha J. Mooney; et al. (Plant Phenome Journal, 2022)
Abstract The spatial arrangement of the root system, termed root system architecture, is important for resource acquisition as it directly affects the soil zone explored. Methods for phenotyping roots are mostly destructive, which prevents analysis of roots over time as they grow. Here, we used X‐ray microcomputed tomography (μCT) to non‐invasively characterize wheat (Triticum aestivum L.) seedling root development across time under high and low nitrate nutrition. Roots were imaged multiple times with the 3D models co‐aligned and timestamped in the architectural plant model OpenSimRoot for subsequent root growth and nitrate uptake simulations. Through 4D imaging, we found that lateral root traits were highly responsive to nitrate limitation in soil with greater lateral root length under low N. The root growth model using all μCT root scans was comparable to a parameterized model using only the final root scan in the series. In a second μCT experiment, root growth and nitrate uptake simulations of candidate wheat genotypes found significant root growth and uptake differences between lines. A high nitrate uptake wheat line selected from field data had a greater lateral root count and length at seedling growth stage compared with a low uptake line.